Islamic Economic Review of The Concept of Employee Wages (Case in Jakarta) - Sania Rakhmah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Research indicates that the concept of remuneration in Islamic economics emphasizes alignment with its principles. Workers are expected to maintain professionalism and avoid fraud. The primary aim of this remuneration concept is to enhance workers' well-being, reflecting a focus on community welfare and humanity rather than just profit. Entrepreneurs are encouraged to treat workers like family, fulfilling all their needs, and embodying the spirit of cooperation (ta'awun), ensuring no harm comes to any party. This ethos promotes collective responsibility in meeting the basic needs of the less fortunate. In the context of Place in Jakarta City, the remuneration model aligns with Islamic economic principles. Employee pay is based on customer percentage, encouraging each worker to contribute to the business's success. Salaries are adjusted according to the employees' skills and the number of customers they serve, resulting in variable wages rather than a fixed amount. This model ensures that remuneration is fair and reflects the employees' contributions, fostering a cooperative and supportive work environment consistent with Islamic values.